When will normalcy return? Exploring the novel COVID-19 spread in the West African Monetary Zone - Ngozi Eunice Egbuna; Maimuna John-Sowe; Santigie M. Kargbo; Ibrahima Diallo; Sani Bawa; Isatou Mendy (West African Journal of Monetary and Economic Integration, 2020)
The increasing uncertainties about the evolving pattern of the novel COVID-19 virus in the absence of a vaccine and the dampening economic effects associated with the containment measures, which have triggered a sharp fall in global commodity prices have raised concerns among policymakers in the WAMZ. This paper seeks to determine the likely time of containment of the pandemic in WAMZ countries and return to normalcy to guide decisions on measures to curtail transmission of the virus. Using three different scenarios and the traditional SEIR (susceptible, exposed, infectious and recovered) epidemiological model, this paper shows that under scenario 1 of continued government intervention and containment measures, all the WAMZ countries may contain the spread of new infections latest in December, 2020. Predictions from scenario 2, which assumes increased testing, contact tracing and isolation of infected and exposed persons suggest that all the six countries are likely to contain the outbreak around October, 2020. By comparison, scenario 3, which assumes increased number of infected cases, owing to weak preventive and control measures, points to delayed containment of pandemic latest by April 2021. The findings underscore the need for the government in the Zone to sustain budgetary spending on health, build capacity to minimise the impact of future pandemic, continue to support public sensitisation campaigns on personal hygiene and social distancing protocols, vulnerable households and businesses to facilitate economic recovery, and develop a regional health strategy to contain contagion across countries.
Keywords: C53; I15; N17; 330; Covid-19 pandemic; SEIR model; preventive measures; WAMZ